What Makes the Gears Go ‘Round? Factors Influencing Bicycling to Suburban Regional Rail Stations - Matthew Graystone; Raktim Mitra (Findings)
In North America, most suburban commuters who use rail transit drive and park at stations, offsetting some benefits of commuter rail. Using passenger survey data collected at three rail stations near Toronto, Canada, we explored the correlates of bicycling for station access trips in a suburban context. Other than automobile ownership, no socio-demographic characteristics were associated with the likelihood of bicycling. Frequency of bicycling for transportation and recreation, preference toward sustainable, and active transportation, and weather-related comfort were correlated with bicycling to a station. Street density along shortest travel route and having to cross a major highway were barriers to bicycling.